Résurgence des premiers parcs victoriens : l’exemple de l’arboretum de Derby - Catherine-Emilie Corvisy (Cahiers Victoriens et Edouardiens)
It was in the 1830s that the need for parks available for public use in the main towns and cities of Britain was identified in order to face an uncontrolled urbanisation. At the same time, the concept of physical health expanded to include moral and social health. The parks, like Derby Arboretum, were seen as a counter attraction to the temptations of the new urban evils. Pastimes in the public parks were considered as “rational” recreation, that is to say activities that were approved of. Like other places, Derby Arboretum provided the visitors with notions of botany. From the 1940s, urban parks were progressively neglected and deserted by the population. It was only in 1995, with the new government of John Major, that parks like Derby Arboretum were renovated. The revival of public parks reveals two main attitudes towards the urban phenomenon: on the one hand, they express the same values as the Victorian parks and, on the other hand, they show how they have adapted themselves to provide for old and new types of urban leisure.